Legal Certainty Regarding Multiple Land Rights Certificates In Indonesia - Fitri, Dian; Mutiara, Upik (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
This study explains and informs about the legal certainty of double land certificates in Indonesia, because this is a legal problem that often arises especially in Indonesia. The research method is by researching sources from Google Scholar, library materials, and secondary materials. The results of the study indicate that the resolution of disputes over double land certificates is prioritized through a mediation process (non-litigation) if it is not proven then it is continued through the court process